HI 1636 (Pusa Vakula), high yielding, bio fortified bread wheat variety for high fertility conditions of Central Zone - SV, Sai Prasad; Singh, Jang Bahadur; Ambati, Divya; M Phuke, Rahul; TL, Prakasha; Mishra, Akilesh Nandan; Sharma, Kailash Chandra; Singh, Anil Kumar; Verma, Dilip Kumar; Singh, Gyanendra Pratap; Sharma, Jai Bhagwan; Singh, Pradeep Kumar; et al. (Journal of Cereal Research, 2023)
HI 1636 (Pusa Vakula), a high yielding bread wheat variety with an average yield of 56.6 q/ha was released by Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops, Government of India vide notification No. S.O.8 (E) dated 03.01.2022 for commercial cultivation under timely sown, irrigated conditions of central wheat growing zone of India.  HI 1636 exhibited seedling resistance to all the prevalent stem and leaf rust pathotypes and postulated to have leaf rust resistance gene Lr24. HI 1636 had an excellent chapati quality and is a “zinc bio-fortified” high yielding bread wheat variety suitable for chapati and biscuit preparations with zinc content of 44.4 ppm and protein content of 11.3%.